A Field Study in Benin to Investigate the Role of Mosquitoes and Other Flying Insects in the Ecology of Mycobacterium ulcerans. - Barnabas Zogo; Armel Djenontin; Kevin Carolan; Jeremy Babonneau; Jean-François Guegan; Sara Eyangoh; Estelle Marion (Public Library of Science (PLoS), 2015)
BACKGROUND:Buruli ulcer, the third mycobacterial disease after tuberculosis and leprosy, is caused by the environmental mycobacterium M. ulcerans. There is at present no clear understanding of the exact mode(s) of transmission of M. ulcerans. Populations affected by Buruli ulcer are those living close to humid and swampy zones. The disease is associated with the creation or the extension of swampy areas, such as construction of dams or lakes for the development of agriculture. Currently, it is supposed that insects (water bugs and mosquitoes) are host and vector of M. ulcerans. The role of water bugs was clearly demonstrated by several experimental and environmental studies. However, no definitive conclusion can yet be drawn concerning the precise importance of this route of transmission. Concerning the mosquitoes, DNA was detected only in mosquitoes collected in Australia, and their role as host/vector was never studied by experimental approaches. Surprisingly, no specific study was conducted in Africa. In this context, the objective of this study was to investigate the role of mosquitoes (larvae and adults) and other flying insects in ecology of M. ulcerans. This study was conducted in a highly endemic area of Benin. METHODOLOGY/PRINCIPAL FINDINGS:Mosquitoes (adults and larvae) were collected over one year, in Buruli ulcer endemic in Benin. In parallel, to monitor the presence of M. ulcerans in environment, aquatic insects were sampled. QPCR was used to detected M. ulcerans DNA. DNA of M. ulcerans was detected in around 8.7% of aquatic insects but never in mosquitoes (larvae or adults) or in other flying insects. CONCLUSION/SIGNIFICANCE:This study suggested that the mosquitoes don't play a pivotal role in the ecology and transmission of M. ulcerans in the studied endemic areas. However, the role of mosquitoes cannot be excluded and, we can reasonably suppose that several routes of transmission of M. ulcerans are possible through the world.